2013
DOI: 10.1177/2325957413488187
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Cushing Syndrome and Secondary Adrenal Insufficiency Related to Concomitant Triamcinolone and Ritonavir Administration

Abstract: Triamcinolone is a long-acting glucocorticoid medication that can be responsible for transient suppression of the hypothalamicpituitary-adrenal (HPA) axis. This physiologic alteration may persist for weeks after repeated or even single localized injection of this agent. However, when this glucocorticoid agent is given to patients receiving the HIV protease inhibitor (PI) ritonavir (RTV), inhibition of their shared cytochrome P450 3A4 degradation pathway leads to an increased bioavailability of triamcinolone, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Methods: The study cohort included 5 patients undergoing fluoroscopically guided intra-articular lumbar facet joint injections at a pain medicine specialty clinic. Blood was collected prior to the injections and on days 1,2,4,6,8, 14,21,28,35, and 42 following the injections.…”
mentioning
confidence: 99%
“…Methods: The study cohort included 5 patients undergoing fluoroscopically guided intra-articular lumbar facet joint injections at a pain medicine specialty clinic. Blood was collected prior to the injections and on days 1,2,4,6,8, 14,21,28,35, and 42 following the injections.…”
mentioning
confidence: 99%
“…Another review identified 13 reports of Cushing's syndrome secondary to triamcinolone injection use in combination with ritonavir. Patients in the review had received a total of one or two doses of the medication, and symptoms usually began 2 or 3 weeks (range 4-42 days) after treatment [24]. In symptomatic patients, CYP3A4 inhibitors and corticosteroids should be stopped.…”
Section: Glucocorticoid Medicationsmentioning
confidence: 99%
“…All of these patients were injected with triamcinolone, except one who was injected with methylprednisolone. [8][9][10][11][26][27][28][29][30] A retrospective review reported an 11% event frequency, with the biggest risk factor being two or more injections within 6 months. 26 Interestingly, a recent randomised controlled trial demonstrated no efficacy advantage of triamcinolone over methylprednisolone for knee osteoarthritis (in a non-HIV population).…”
Section: Current Evidence On Individual Glucocorticoids By Route Inhaledmentioning
confidence: 99%